Alumni Relations in Times of Pandemic: Disruption is the Mother of Invention - Grceva, Nena (ICAReAlumni Conference Proceedings, 2020)
Goal: Pair up current CEU students with alumni “buddies” in order to help students maintain a writing routine and focus and submit their thesis on time.